Evaluating Surgical Decision-making in Nonsyndromic Sagittal Craniosynostosis Using a Digital 3D Model. Issue 5 (21st May 2021) - Hughes, Christopher D.; Langa, Olivia; Nuzzi, Laura; Staffa, Steven J.; Proctor, Mark; Meara, John G.; Ganske, Ingrid M.
Abstract : Background: Surgical correction of craniosynostosis addresses potentially elevated intracranial pressure and the cranial deformity. In nonsyndromic sagittal synostosis, approximately 15% of patients have elevated intracranial pressure. The decision to operate therefore likely reflects a combination of aesthetic goals, prevention of brain growth restriction over time, surgeon training and experience, and parental expectations. This study examines clinical factors that influence surgical decision-making in nonsyndromic sagittal synostosis. Methods: An online survey sent to craniofacial and neurosurgeons presented 5 theoretical patients with varying severities of sagittal synostosis. For each cephalic index, 4 separate clinical scenarios were presented to assess influences of parental concern and developmental delay on the decision to operate. Results: Fifty-six surveys were completed (response rate = 28%). Participants were predominantly from North America (57%), had over 10 years of experience (75%), and performed over 20 craniosynostosis procedures annually (50%). Thirty percent of respondents indicated they would operate regardless of head shape and without clinical and/or parental concern. Head shape was the greatest predictor of decision to operate ( P < 0.001). Parental concern and developmental delay were independently associated with decision to operate ( P < 0.001). Surgeons with more experience were also more likely to operate across all phenotypes (OR: 2.69, P < 0.004). Conclusions: Surgeons responding to this survey were more strongly compelled to operate on children with nonsyndromic sagittal craniosynostosis when head shape was more severe. Additional factors, including parental concern and developmental delay, also influence the decision to operate, especially for moderate phenotypes. Geographic and subspecialty variations were not significant.